IMPLEMENTASI MANAJEMEN PENDIDIKAN ISLAM DALAM KONSEP MANAJEMEN HUBUNGAN MASYARAKAT DENGAN SEKOLAH - Rais, Wendi (ECONOS Jurnal Ekonomi dan Sosial, 2019)
The most important thing in the management of Islamic education is the management components. One of them is public relations management (public relations) because the school is in the midst of the community and always relates to establishing pedagogical and sociological cooperation that benefits both parties. Management is very important for the success of an organization. PR is a series of organized activities such as a series of integrated campaigns or programs, and all of them are ongoing and regular. The community as a third educational institution after family and school has a considerable role in the ongoing activities concerning education problems. Given the importance of the role of public relations in educational institutions and the gap between theory and reality in the field (problems), this paper will discuss "Implementation of Islamic Education Management in the Concept of Public Relations with School Management. Conclusion This paper is; First, the Implementation of Islamic Education Management in the Concept of Management of Public Relations with Schools will run optimally, if it is planning, organizing, implementing and monitoring properly. Second, Supporting Factors in the Implementation of Islamic Education Management in the Concept of Management of Public Relations with Schools is a harmonious relationship between school members and the surrounding community in particular and the wider community in general which is applied through student activities especially extracurricular activities. The inhibiting factors that exist in the implementation of public relations are located in the weak quality of human resources students and teachers, lack of infrastructure and funds